'Fitna' is surely trash - Abd Razak, Dzulkifli (2008)
FITNA (or fitnah) is an Arabic word that has become wellaccepted in the Malay vocabulary. Its common usage gives a negative connotation bordering on “slander”, “malice” or “backbiting”, especially in the context of spreading mischief and falsehood. Fitna is therefore frowned upon in Islam since it often results in not only disrepute, but could also cause suspicion and animosity. In these days of instant communication, fitna has a greater consequence for societal wellbeing. In many ways, fitna is a global phenomena, not confined to Muslims.